Ocular Histopathological Findings in Semi-Domesticated Eurasian Tundra Reindeer (Rangifer tarandus tarandus) with Infectious Keratoconjunctivitis after Experimental Inoculation with Cervid Herpesvirus 2 - Sanchez Romano, Javier; Sørensen, Karen Kristine; Larsen, Anett Kristin; Mørk, Torill; Tryland, Morten (Viruses, 2020)
Infectious keratoconjunctivitis (IKC) is a common transmissible ocular disease in semi-domesticated Eurasian tundra reindeer ( Rangifer tarandus tarandus ). In large outbreaks, IKC may affect tens of animals in a herd, with the most severe cases often requiring euthanasia due to the destruction of the affected eyes and permanent blindness. An experimental inoculation with cervid herpesvirus 2 (CvHV2), alone or in combination with Moraxella bovoculi , demonstrated that CvHV2 has the ability to cause clinical signs of IKC in previously unexposed reindeer. Tissues collected from upper and lower eyelids, lacrimal gland and cornea, were processed for light and transmission electron microscopy. Histopathological analysis of the eyes inoculated with CvHV2 showed widespread and severe pathological findings. Mucosal tissues from these eyes showed fibrinous and purulent exudates, hyperemia, hemorrhages, necrosis, vascular thrombosis, vascular necrosis, infiltration of mononuclear cells and neutrophils, and lymphoid follicle reaction, which matches the described histopathology of IKC in reindeer. Characteristic alpha-herpesvirus particles matching the size and morphology of CvHV2 were identified by transmission electron microscopy in the conjunctival tissue. The quantification of viral particles by qPCR revealed high copy numbers of viral DNA in all CvHV2 inoculated eyes, but also in the non-inoculated eyes of the same animals. The histopathology of eye tissues obtained from the CvHV2 inoculated reindeer and the lack of inflammation from bacterial infection, together with the detection of CvHV2 DNA in swabs from the inoculated and non-inoculated eyes of the same animals, verified that CvHV2 was the primary cause of the observed histopathological changes.